1989- Beef is safe. 1996- Not.. (2000) - Unknown
Abstract : A sharply critical government report on the administration of mad-cow disease research leads the news from Nature this week. Science also covers the story, but they lead with librarians protests over a proposed merger of two science publishing giants.